The Morphological Stenosis Pattern of the Caroticoclinoid Foramen - Ioannis Paschopoulos; George Triantafyllou; Panagiotis Papadopoulos-Manolarakis; Sabino Luzzi; Nektaria Karangeli; George Tsakotos; Renato Galzio; Maria Piagkou (Diagnostics)
Background: The caroticoclinoid bar (CCB) or caroticoclinoid foramen (CCF) represents a well-described ossified variant of the skull base. It corresponds to an osseous bridge (resulting after homonymous ligament ossification) between the anterior and middle clinoid processes (ACPs and MCPs) surrounding the internal carotid artery (ICA)’s cavernous segment. Although extensive research has been performed on this clinically significant entity, only a few studies have been conducted on its effect on the ICA. The current study on dried skulls, using computed tomography (CT) and computed tomography angiography (CTA) scans, aimed to investigate the CCB’s presence and potential morphological stenosis patterns. Methods: One hundred (100) dried adult skulls and one hundred sixty (160) skulls from CT scans of patients were obtained (a total of 520 observations). To further calculate the ICA diameter (at the ACP-MCP region) and correlate the resulting dimeters with all potential morphological stenosis patterns of the CCB, thirty (30) CTAs of patients free of the variant were selected. Results: Concerning the osseous pattern morphology, of the total of 520 sides, the CCB was identified in 17.1%, the complete variant (creating a caroticoclinoid foramen-CCF) was calculated in 11.5%, and the incomplete one was calculated in 5.6%. No side, sex, or age impact was identified for the CCB presence. Concerning the ICA dimensions, its diameter was calculated to be between 4 and 5 mm. Thus, we observed three morphological stenosis patterns of the CCF. A low-risk pattern of stenosis (>5 mm diameter) was observed in 40 CCFs (44.9%), an intermediate risk of stenosis (4–5 mm diameter) in 38 CCFs (38.2%), and a high risk of stenosis (<4 mm diameter) was depicted in 15 CCFs (16.8%). Conclusions: In the present study, we investigated the CCF presence and potential morphological stenosis patterns by calculating and correlating the ICA diameter. In 16.8% of the current sample with CCFs (irrespective of their morphology), we observed that the ICA is probably at a high risk of compression. Radiologists and neurosurgeons intervening in the area should preoperatively diagnose the possibility of ICA compression in this area.